O pobre intelectual: Manuel Lourosa, astronomy, and the political restoration of Portugal in the seventeenth century - Carolino, L. M.; Camenietzki, C. (Cultural hegemony in a scientific world: Gramscian concepts for the history of science, 2020)
In the early 1640s, in the aftermath of the coup d’état that brought an end to six decades of Habsburg rule over the Portuguese crown (the so-called Restauração, or Restoration, of 1640), the Portuguese Inquisition was asked to censor a book expressing strong opinions in favour of the new political status quo: ‘A Mathematical Prediction. A Political, Physiological, Democratic, Ethical, Aristocratic, and Theological Treatise’ [Alvitre mathematico. Tratado politico, physiologico, democratico, ethico, aristocratico e theologico], by the physician Manuel Gomes Galhano Lourosa.1 Despite being an ecclesiastical tribunal, the Portuguese Inquisition worked largely as a ‘state’ tribunal,2 one part of the collection of tribunals and councils that formed the Portuguese political system during the ‘ancien regime’.3 This was also not the first time that Lourosa had faced this coercive state apparatus4 and again having his book rejected and this time with its author criticised: ‘the poor man does not understand anything’, the censor stated.5 The publication of Lourosa’s A Mathematical Prediction was specifically declined on the grounds that it virtually subverted the monarchical order.